A Rare Case of Synchronous Gastric Signet Ring Cell Adenocarcinoma Metastasis at the right colon angle - Baccouche, Seifeddine; Achref, Sarraj; Hajri, Mohamed; Rania, Osman; Ferjaoui, Wael; Lahmer, Ahlem; Slama, Sana ben; Bacha, Dhouha (Journal of Advances in Internal Medicine, 2022)
Although it can affect any part of the gastrointestinal system, signet ring cell carcinoma (SRC) is a common malignant entity of stomach cancers. We discuss the case of a patient who had a prior history of gastric adenocarcinoma with signet ring cells, for which he underwent a partial gastrectomy with a gastro-jejunal anastomosis. Four months after surgery, he presented an acute postoperative blockage. Operative findings and pathology exams concluded the presence of SRC at the right angle of the colon. In patients with obstructive symptoms after surgery for SRC neoplasms of the stomach, the possibility of a second lesion should be considered among the differential diagnoses.